Clinical treatment outcomes of hypertensive emergency patients: Results from the hypertension registry program in Northeastern Thailand. Issue 3 (7th December 2020) - Kotruchin, Praew; Pratoomrat, Wachira; Mitsungnern, Thapanawong; Khamsai, Sittichai; Imoun, Supap
Abstract: Hypertensive emergency care is a challenge in clinical practices due to vital organ complications that may lead to unfavorable outcomes if left untreated. The objectives of this study were to determine the prevalence, clinical characters, treatment, and outcomes of hypertensive emergency patients. A retrospective cohort study was conducted at a university hospital in Northeast Thailand from January 2016 to December 2019. Hypertensive crises patients were consecutively registered to the Hypertension Registry Program. There were 263 674 patients who were admitted to the ER, 60, 755 of whom had BP ≥ 140/90 mm Hg and 1, 342 of whom were diagnosed with a hypertensive emergency (127 per 100 000 patient‐year). The mean age was 66 years old, and 52.1% of the registered patients were men. The most common target organ damage was caused by stroke (49.8%), followed by acute heart failure (19.3%), and then by acute coronary syndrome (6.5%). Intravenous antihypertensive medication was given in 42.1% of the patients, and 80% were admitted to the hospital. The in‐hospital mortality rate was 1.6%. In conclusion, hypertensive emergencies were not uncommon among the emergency patients. Strokes caused the most common target organ damage. Although there was a high hospital admission rate, the mortality rate was low.